Antecedent of lack of proficiency and the need for an automated financial plan for the course entrepreneurship creativity and innovation. Issue 1 (14th August 2021) - Thottoli, Mohammed Muneerali
Abstract : Purpose: This study aims to analyze antecedents of students' lack of proficiency (in preparing financial statements, cash flow statements, cost volume profit analysis and budgeting) and the need for an automated financial plan (AFP) for the course entrepreneurship creativity and innovation within Higher Educational Institutions (HEIs) in Oman. Design/methodology/approach: The study used a set of four instrument items containing questionnaires to measure the variables in this study. A cross-sectional study was carried out at various universities and colleges in Oman during the year 2020, comprising 174 students from different majors. The results were analyzed using structural equation modelling-partial least squares. Findings: The findings of the study suggest that the students in the universities and colleges should be educated and facilitated to enable them to gain more knowledge in finance/accounting through an AFP and, thus, warrants preparation of fair financial estimation for their innovative business project. A majority of students strongly support the need for implementing an AFP for their compulsory course, entrepreneurship creativity and innovation in HEIs in Oman. Research limitations/implications: This research is restricted to AFPs for the students in Oman who study the course entrepreneurship creativity and innovation. It is recommended that future study may extend to automated business plans for the students to improve their practical knowledge pertinent to the readiness of Omani students, as well as to give material transformation of internal environments in HEIs. Practical implications: Unique AFP for university and college students for their compulsory course, entrepreneurship creativity and innovation provide important resources for policymakers responsible for HEIs, allowing them to improve the quality of preparing a financial plan for their innovative business ideas and new business start-ups. Originality/value: There has been little discussion about the need for an AFP for the students who study the course entrepreneurship creativity and innovation. This study analyzes accounting standards as antecedents about students' lack of proficiency towards an AFP for the course entrepreneurship creativity and innovation of universities and colleges in Oman which tries to fill this gap in the existing research. Hence, this study is considered as a novel approach that has not been broadly discussed in the earlier research.